Evolutionary, not revolutionary – logics of early design energy modelling adoption in UK architecture practice. (4th May 2017) - Oliveira, Sonja; Marco, Elena; Gething, Bill; Organ, Samantha
ABSTRACT: This paper examines the effects of early stage design energy modelling technology on architects' design practice. Energy analysis in design has traditionally been the domain of the building services engineer with emphasis placed on verifying established building simulation models at late stages in design. Recently, however, with advances in digital design media, leading architectural firms are acquiring in-house design simulation for energy modelling. The effects of broadening the use of energy modelling technology on architecture design practice or the design process are, however, poorly understood. Industry and academic attention has been gathering on the topic of building performance simulation with most of the focus placed on standardizing the wide array of tools and narrowing the broad spectrum of analysis parameters. Few discussions examine approaches to energy analysis across the diverse design settings and the principles, assumptions and identities designers negotiate. The analysis draws on institutional theory utilizing semi-structured interviews and focus group sessions with 26 participants across 4 large international architecture firms. Preliminary findings indicate differing organizational, team and project approaches with an emphasis placed on legitimating established design assumptions across the firms. The implications of the findings are twofold. First, the analysis provides an initial overview of how early stage design energy modelling is considered in design in architecture practice in the UK. Second, the paper provides an understanding of how architects negotiate meaning on energy in design. There are also implications for energy policy development in the context of the built environment particularly concerning building performance.